ANALISIS PENGARUH STRUKTUR KEPEMILIKAN TERHADAP PEMILIHAN AUDITOR PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ivone, Ivone; Noorasyikin, Noorasyikin (Global Financial Accounting Journal, 2020)
Feeble financial governance is one of the causes of frequent financial scandals. Good financial governance is developed into a balancing system to minimize the presence of inappropriate information in the financial statements. As one of the external mechanisms of corporate governance, external audit plays an important role in strengthening the trust and financial information of the company in terms of providing an independent check on financial information provided by management. The ownership structure of the company can be a factor in selecting an audit company based on the desired quality measurement. In that case, the factor of selecting external auditors by the influence of ownership structure becomes an important focus in this study. Focusing on Indonesia, this study used a sample of 429 companies listed on the Indonesia Stock Exchange during 2014-2018. The data used in the form of annual reports and company financial statements published in general in official sources. Testing assumptions and data analysis are completed by the logistic regression method. The findings obtained from the test are the presence of concentrated ownership and foreign ownership in the company may have significant positive effect on the selection of auditors but for controlling family ownership has the opposite result, namely negative relationship, and no significant effect on managerial ownership of the elected auditor.